(3MGTjI Ydi GdahGFO GdVjGFjI TQM GdcGajI ddLGejs - (3GdCSaQGjjfj, GdYUGe, EHQGgje Hf eMeO Hf YQH TGg, J(B945(3g`s ((3eOQSI YOGSjIs)
(3ChdgG (B:s
(3jG gGOjG dSGdc eSGdc eMGeOc hHYO ajbhdEHQGgje Hf eMeO Hf YQH TGg GdCSaQGfj YUGe GdOjf gPg MhGTj ddahGFO GdVjGFjIs
(3BNQgG (B:s
(3jhLH Cf dG jcJH GdNajaI GdJj de jaJM eG bHdgG hjcJH CdaG EPG GfaJM eG bHdgG acJGHJgG Ydi NdGa GdbjGSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 66s
(3eYLe GdeDdajf(B: 1 / 67s
(3cTa GdXfhf(B: 2 / 1372s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs